Educomunicação e jornalismo: possibilidade de prática educativa para o exercício do jornalismo cidadão - Silva, Christiane Pitanga Serafim da (2020)
In the first semester of Journalism studies at UFU Educommunication has been experienced as an educational practice and as a process of sharing and producing knowledge in a creative and critical way, in a dialogical, horizontal and democratic relationship between teachers, students and communities out of the university for media production. This research explores, from the students' perspective, to what extent and how the learning resulting from this dialogue contribute to the journalistic qualifications and to exercise citizen journalism. Therefore, a review of literature on Educommunication and citizen journalism was carried out to evaluate the semi-structured interviews conducted with the students. This is a qualitative research and it was developed according to Paulo Freire's dialogical and problematizing education, using dialectics as the method of analysis. Results of this study substantiate the belief that the educommunicative process can develop a critical knowledge about Journalism and make the practice of citizen journalism easier. However, the educommunicative project as an educational practice is not enough to break with the determinism neither of the market nor of the Journalism studies at UFU itself. This research advances the idea that, for this, Educommunication would need to be a transdisciplinary educational practice during all the graduation on Journalism.